Normalizing serum hepcidin but not α-1-antitrypsin level during effective treatment of chronic hepatitis C - Rogalska-Taranta, Magdalena; Jaroszewicz, Jerzy; Flisiak, Robert (Clinical and Experimental Hepatology, 2017)
Aim of the study: We investigated the impact of pegylated interferon α-2 in combination with ribavirin (PEG-IFNα/RBV) treatment on hepcidin and α-1-antitrypsin concentrations in the serum of patients with chronic hepatitis C. Material and methods : We measured serum concentrations of hepcidin, prohepcidin and α-1-antitrypsin by enzyme-linked immunosorbent assays in patients with chronic hepatitis C before and during antiviral therapy. Results : Hepcidin concentrations were increased in both genotype 1b and 3a hepatitis C virus (HCV) infected patients as compared with the control group. During treatment of patients infected with genotype 1b HCV hepcidin levels gradually declined, reaching significantly lower values at the treatment termination than before therapy. Treatment responders showed an increased concentration of hepcidin at week 4 of therapy and a subsequent decrease to values significantly lower than observed among non-responders at week 48 of treatment. α-1-antitrypsin concentration was not affected by the treatment efficacy. Conclusions : Successful therapy of patients persistently infected with HCV was associated with restoration of serum hepcidin concentration to values similar to the control group. Differential dynamics of hepcidin during PEG-IFNα/RBV therapy in responders and non-responders might indicate the direct influence of viral eradication on iron homeostasis.